Ideological polarization during a pandemic: Tracking the alignment of attitudes toward COVID containment policies and left-right self-identification - Dochow-Sondershaus, Stephan (Frontiers in Sociology, 2022)
Research on opinion polarization has focused on growing divides in positions towards political issues between the more politically and ideologically engaged parts of the population. However, it is fundamentally difficult to track the alignment process between ideological group identity and issue positions because classically controversial political issues are already strongly associated with ideological or partisan identity. This study uses the COVID pandemic as an unique opportunity to investigate polarizing trends in the population. Pandemic management policies were not a politicized issue before COVID, but became strongly contested after governments all across the world initiated policies to contain the pandemic. We use data from the Austrian Corona Panel Project (ACPP) to track trajectories in attitudes towards current COVID measures over the course of more than a year of the pandemic. We differentiate individuals by their ideological self-identity as measured by left-right self-placement. Results suggest that all ideological groups viewed the containment measures as similarly appropriate in the very beginning. However, already in the first weeks, individuals who identify as right-wing increasingly viewed the policies as too extreme, whereas centrists and left-wing identifiers viewed them as appropriate. Opinion differences between left-wing and right-wing identifiers solidified over the course of the pandemic, while centrists fluctuated between left and right self-identifiers. However, at the end of our observation period, there are signs of convergence between all groups. We discuss these findings from the perspective of theoretical models of opinion polarization and suggest that polarization dynamics are likely to stop when the political context (salience of certain issues and concrete material threats) changes.